Overexpression of BnPCS1, a Novel Phytochelatin Synthase Gene From Ramie (Boehmeria nivea), Enhanced Cd Tolerance, Accumulation, and Translocation in Arabidopsis thaliana - Zhu, Shoujing; Shi, Wenjuan; Jie, Yucheng (Frontiers in Plant Science, 2021)
Phytochelatins (PCs) play important roles in the detoxification of and tolerance to heavy metals in plants. The synthesis of PCs is catalyzed by phytochelatin synthase (PCS), which is activated by heavy metal ions. In this study, we isolated a PCS gene, BnPCS1, from the bast fiber crop ramie (Boehmeria nivea) using the RACE (rapid amplification of cDNA ends) method. The full-length BnPCS1 cDNA is 1,949 bp in length with a 1,518 bp open reading frame (ORF) that encodes a 505 amino acid protein. The deduced BnPCS1 protein has a conserved N-terminus containing the catalytic triad Cys58, His164, Asp182 and a flexible C-terminal region containing a C371C372QETC376VKC379 motif. The BnPCS1 promoter region contains several cis-acting elements involved in phytohormone or abiotic stress responses. Subcellular localization analysis indicates that the BnPCS1-GFP protein localizes to the nucleus and the cytoplasm. Real-time PCR assays show that the expression of BnPCS1 is significantly induced by cadmium (Cd) and the plant hormone abscisic acid (ABA). Overexpression lines of BnPCS1 exhibited better root growth and fresh weight, lower level of MDA and H2O2, and higher Cd accumulation and translocation factor compared to the WT under Cd stress. Taken together, these results could provide new gene resources for phytoremediation of Cd-contaminated soils.